2003
DOI: 10.1128/mcb.23.21.7460-7474.2003
|View full text |Cite
|
Sign up to set email alerts
|

PU.1 and pRB Interact and Cooperate To Repress GATA-1 and Block Erythroid Differentiation

Abstract: PU.1 and GATA-1 are two hematopoietic specific transcription factors that play key roles in development of the myeloid and erythroid lineages, respectively. The two proteins bind to one another and inhibit each other's function in transcriptional activation and promotion of their respective differentiation programs. This mutual antagonism may be an important aspect of lineage commitment decisions. PU.1 can also act as an oncoprotein since deregulated expression of PU.1 in erythroid precursors causes erythroleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
78
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 76 publications
8
78
1
Order By: Relevance
“…13 PU1-GATA1 antagonism is a well documented mechanism in myeloid versus erythroid differentiation. 45 However, our preliminary results suggest that Ikaros does not significantly affect human myeloid differentiation.…”
Section: Discussionmentioning
confidence: 41%
“…13 PU1-GATA1 antagonism is a well documented mechanism in myeloid versus erythroid differentiation. 45 However, our preliminary results suggest that Ikaros does not significantly affect human myeloid differentiation.…”
Section: Discussionmentioning
confidence: 41%
“…(GATA) inhibits the function of GATA (PU.1), resulting in dominion by itself, during the development from hematopoietic stem cells toward the monocyte (erythrocyte/megakaryocyte) lineage (21)(22)(23)(24)(25)(26)(27)(28). In contrast, PU.1 and GATA1/GATA2 exhibit a cooperative function in mast cells, as follows: 1) PU.1 and GATA2 cooperatively induce mast cell development (20); 2) PU.1 and GATA1 synergistically transactivate cell type-specific gene regulation in mast cells (5,29); and 3) PU.1 is required for GATA1 expression in mast cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of such stoichiometry can operate in the absence of DNA-binding sites and therefore the transcription factors can either mutually block each other's accession to DNA 56 or can coexist on DNA and block each other's transactivation by protein-protein interactions within chromatin. 49,57 Initially it was thought that PU.1 prevents binding of GATA-1 to DNA as shown by electrophoretic mobility shift assays. 56 However, by using DNase-I footprinting such inhibition was observed at a non-physiological molar ratio (20:1) whereas at a 1:1 ratio PU.1 actually altered the GATA-1-generated footprint near the GATA-1-binding site thereby arguing for the possibility that both PU.1 and GATA-1 coexists on DNA.…”
Section: Pu1 and Gata-1 Interact During Early Hematopoietic Cell Decmentioning
confidence: 99%
“…56 However, by using DNase-I footprinting such inhibition was observed at a non-physiological molar ratio (20:1) whereas at a 1:1 ratio PU.1 actually altered the GATA-1-generated footprint near the GATA-1-binding site thereby arguing for the possibility that both PU.1 and GATA-1 coexists on DNA. 57 The GATA-1 reporter construct was transfected into U2OS cells, a human osteosarcoma cell line, and in this in vivo assay it clearly responded positively to GATA-1 and negatively following the addition of PU.1. 57 Chromatin immunoprecipitation studies showed the co-occupancy of both PU.1 and GATA-1 proteins to DNA 57 and that this co-occupancy was dependent on the presence of both a GATA-1 cis-binding site and the Ets domain on the PU.1 protein.…”
Section: Pu1 and Gata-1 Interact During Early Hematopoietic Cell Decmentioning
confidence: 99%
See 1 more Smart Citation